Isoenzyme variation in the leaf-cutting ants Acromyrmex heyeri and Acromyrmex striatus (Hymenoptera, formicidae) - Diehl,Elena (2002)
This is the first study of isoenzyme variability in the leaf-cutting ants (Myrmicinae, Attini) Acromyrmex heyeri (Forel, 1899) and A. striatus (Roger, 1863) which are common throughout the southern Brazilian state of Rio Grande do Sul. We studied the alloenzyme variability of malate dehydrogenase (MDH), alpha-glycerophosphate dehydrogenase (alpha-GPDH) and amylase (AMY) in 97 colonies of A. heyeri and 103 colonies of A. striatus. Five loci were found for these enzyme systems, one locus (Amy-1) being monomorphic in both species and four loci (Mdh-1, alpha-Gpdh-1, Amy-2, and Amy-4) being polymorphic. For each species there were exclusive alleles for the Mdh-1 and Amy-2 loci and differences were also found in the allele frequencies for the other polymorphic loci. Ontogenetically different gene activity was detected for the MDH and alpha-GPDH systems, with between-caste differences, probably related to flight activity, also being found for alpha-GPDH.